Exploration of Methods for Solubility Studies of Amyloid Beta - Stemme,Elin (2024)
The protein amyloid beta (Aβ) is a major component in the amyloid plaques associated with Alzheimer’s disease. This project concerns the most common version of this protein, Aβ40. In a supersaturated solution, Aβ40 monomers can aggregate to form amyloid fibrils. The solubility of an amyloid protein is equal to the concentration of the monomeric peptide in solution at equilibrium. To study the solubility, with the ambition to better understand the driving forces of the fibril formation, there is a need for reliable methods to determine the monomer concentration at equilibrium. In this project, three such methods were explored. The first quantification method utilised the fluorescent probe o-phtalaldehyde (OPA), which reacts with primary amines in the peptide. The second method was high-performance liquid chromatography with mass spectrometry (HPLC-MS), which gave results based on both UV absorbance and total ion count after separation based on hydrophobicity. Both OPA and HPLC-MS quantification required the monomers to be separated from the fibrils, prior to measurements. Additionally, the samples were incubated in plate readers with ThT prior to the separation and quantification. The third and final quantification method was nuclear magnetic resonance spectroscopy (NMR). In NMR, the concentration of the monomers was calculated both based on the initial concentration and on an external standard. NMR reported the highest apparent solubility, OPA an intermediate value (with an increase as the total Aβ40 concentration increased) and HPLC-MS reported the lowest apparent solubility. Kinetic traps, adsorption and protein degradation/modification were suggested to contribute to the differences in the results. Future experiments should include incubating with shaking, measuring with NMR and then calculating with external standard. Furthermore, it is necessary to repeat the experiments and evaluate their accuracy and precision.
Keywords: amyloids; solubility; amyloid beta; biotechnology